2007
DOI: 10.4037/ajcc2007.16.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Consequences of Nonadherence to Hemodialysis Regimens

Abstract: Adherence to fluid restrictions and dietary and medication guidelines as well as attendance at prescribed hemodialysis sessions of a hemodialysis regimen are essential for adequate management of end-stage renal disease. A literature review was conducted to determine the prevalence and consequences of nonadherence to the different aspects of a hemodialysis regimen and the methodological obstacles in research on nonadherence. Nonadherence to the prescribed regimen is a common problem in hemodialysis and is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
179
1
24

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(207 citation statements)
references
References 78 publications
3
179
1
24
Order By: Relevance
“…The range of estimates of nonadherence in the HD population is due to the lack of standardized definitions . Dichotomizing adherence is particularly contentious.…”
Section: Assessing Adherencementioning
confidence: 99%
See 3 more Smart Citations
“…The range of estimates of nonadherence in the HD population is due to the lack of standardized definitions . Dichotomizing adherence is particularly contentious.…”
Section: Assessing Adherencementioning
confidence: 99%
“…For example, while it is agreed that IDWG is a suitable indicator of fluid adherence and sodium intake , multiple cut‐off points have been used. One common classification for nonadherence is an average IDWG ≥2.5 kg , with other cut‐offs ranging from 1 to 3.0 kg . Significantly, IDWG is influenced by several factors including residual kidney function , dry weight and nutritional state .…”
Section: Assessing Adherencementioning
confidence: 99%
See 2 more Smart Citations
“…Denhaerynck et al . () has identified that the lack of officially adopted renal diet adherence criteria has led mainly to the use of biochemical markers and self‐reported scoring (0–6: representing poor to excellent) for this purpose. In the present review, we aim to study the dietary adherence of children with CKD, after they and their parents were provided with guidance regarding nutrition.…”
Section: Assessment Of Dietary Adherencementioning
confidence: 99%